Analisis Potensi Ekonomi Lingkar Wilis Sebelum dan Sesudah Covid-19 - Amirusholihin Amirusholihin; Lienggar Rahadiantino (Inspirasi Nusantara, 2022)
This study aims to analyze the economic potential of the six districts that were passed by the Wilis Ring Road before and after the Covid-19 pandemic. We analyze which sectors are the mainstays of these regencies. The data used is PRDB data by business field obtained from the East Java Central Statistics Agency (BPS) for 2010-2021. This study uses the Location Quotient (LQ) analysis technique. The results of this study indicate that there have been no significant changes in the economic structure in the six Wilis ring areas. There were the same five base sectors in the six districts around Wilis before Covid and four base sectors after Covid-19. The base sectors that have survived the Covid-19 pandemic are the Agriculture, Forestry and Fisheries Sectors, the Real Estate sector; the Government Administration sector, the Defense and Compulsory Social Security Sector, and the Education Services Sector.